Class II biocompatible E-Shell 300 3D printing material causes severe developmental toxicity in Danio rerio embryos and reduced cell proliferation in vitro – implications for 3D printed microfluidics. Issue 27 (4th May 2021) - Nejedlá, Zuzana; Poustka, David; Herma, Regina; Liegertová, Michaela; Štofik, Marcel; Smejkal, Jiří; Šícha, Václav; Kaule, Pavel; Malý, Jan
Abstract : E-Shell 300 3D-printed material demonstrated a considerable negative impact on cell proliferation and severe developmental toxicity due to release of surfactant residues. Post-treatment with ethanol improved the biocompatibility of the material. Abstract : Additive manufacturing is a new technology that represents a highly promising, cheap, and efficient solution for the production of various tools in the biomedicine field. In our study, the toxicity of the commercially available E-Shell 300 series photopolymer, which is used in the manufacture of hearing aids and other implants and which could be potentially exploited in microfluidic device fabrication, was tested using in vivo and in vitro biological models. We examined B14 cell proliferation in direct contact with the three-dimensional (3D)-printed material as well as in water extracts to evaluate in vitro cytotoxicity. Similarly, in vivo tests were performed using an OECD-standardized fish embryo acute toxicity (FET) test on Danio rerio embryos in direct contact with the material and in extracts as well. Despite E-Shell 300 3D-printed material being declared as class-IIa biocompatible, in the case of direct contact with both biological models, the results demonstrated a considerable negative impact on cell proliferation and severe developmental toxicity. In this study, up to 84% reduced cell proliferation in vitro and 79% mortality of in vivo models were observed. In contrast, a negligible toxic influence of E-Shell 300 water extracts was present. Four different post-processing treatments to reduce the toxicity were also tested. We observed that post-printing treatment of 3D-printed material in 96% ethanol can reduce embryonic mortality in the FET test by 71% and also completely eliminate negative effects on cell proliferation. We analyzed leachates from the polymeric structures by mass spectrometry (MS) and nuclear magnetic resonance (NMR) spectroscopy, and we discovered the presence of surfactant residues. In summary, our results indicate the importance of biocompatibility testing of the 3D printing photopolymer material in direct contact with the given biological model. On the other hand, the possibility of eliminating toxic effects by an appropriate post-processing strategy opens the door for broader applications of E-Shell 300 photopolymers in the development of complex microfluidic devices for various biological applications.